OPEN INNOVATION AS A NEW PARADIGM IN RESEARCH AND BUSINESS - Slobodan Malbasic; Aleksandar Aleksic (Proceedings on Engineering Sciences, 2019)
In order to gain the competitive advantage on the market, companies need to seek for ways for improvement of their process and products in continuous manner. The real improvement comes with innovation. Innovation is explained as the application of new ideas to the all aspects of activities that companies perform. In order to clarify the phenomena of innovation, this paper explains new paradigm in the business – open innovation, benefits and shortcomings of this concept, relation with quality, as well as set of different accompanying terms (crowd sourcing, off-spin) and dimensions of openness (inbound, outbound). Having in mind that defense industry sector is not staying immune to this concept, its innovative approach is explained also in an example. Findings in this paper relays on variety of articles and reports published to support this new paradigm.